2001
DOI: 10.1177/107906320101300104
|View full text |Cite
|
Sign up to set email alerts
|

Sex As a Coping Strategy and Its Relationship to Juvenile Sexual History and Intimacy in Sexual Offenders

Abstract: The current research examined the hypothesis that sexual activity functions as a coping strategy for sexual offenders. A 16-item scale, the Coping Using Sex Inventory (CUSI), was developed to assess the presence of and the degree to which sex was used to deal with problematic situations. Sexual offenders consistently reported using sexual activities, both consenting and nonconsenting, as a coping strategy to deal with stressful and problematic situations. In the first study, when compared to nonsexual violent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
137
2
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(156 citation statements)
references
References 20 publications
9
137
2
8
Order By: Relevance
“…This is supported within the sex offender literature (e.g. Cortoni & Marshall, 2001;Mann, Hanson & Thornton, 2010;Seghorn & Ball, 2000) in which sexual outlets are recognised as 'self medication' or a coping strategy to overcome depression, anxiety or negative emotional states. Whether these effects of reduced depressive symptomology, and those of reduced arousal and preoccupation, are direct or indirect effects of the medication is currently unknown as there is difficulty in determining which is reduced first, but nevertheless a reduction in all was apparent.…”
Section: Sub-theme 13: Managing Negative Emotionssupporting
confidence: 50%
“…This is supported within the sex offender literature (e.g. Cortoni & Marshall, 2001;Mann, Hanson & Thornton, 2010;Seghorn & Ball, 2000) in which sexual outlets are recognised as 'self medication' or a coping strategy to overcome depression, anxiety or negative emotional states. Whether these effects of reduced depressive symptomology, and those of reduced arousal and preoccupation, are direct or indirect effects of the medication is currently unknown as there is difficulty in determining which is reduced first, but nevertheless a reduction in all was apparent.…”
Section: Sub-theme 13: Managing Negative Emotionssupporting
confidence: 50%
“…Moreover, it appears that behavioral manifestations of coping were more prevalent in child molesters than in the control males, suggesting difficulty in adjusting to stressors at an affective or cognitive level, and a tendency to cope with internal or ex- ternal stressors behaviourally. This finding is contrary to that of Cortoni and Marshall (2001) who found, using a questionnaire, that child abusers use more emotion-focused coping. While a number of differences between the two studies could explain this disparity, a major difference was that Cortoni and Marshall focused on sex as a coping strategy, not on all possible coping schemes.…”
Section: Discussioncontrasting
confidence: 56%
“…According to the authors, these coping strategies are dysfunctional and they contribute to dysphoric mood states and increase the risk of relapse. In another study, Cortoni and Marshall (2001) found that pedophiles use more emotion-focused coping, which involves an emotional response to a problem or stressor. A recent study (Serran, Moulden, Firestone, & Marshall, 2007) investigated change in coping after a cognitive-behavioral therapy with relapse prevention.…”
Section: Introductionmentioning
confidence: 95%
“…Even if diagnosed mental illness are not associated with future offending among adolescent offenders [44] [45], the symptoms associated with these disorders and inability to regulate emotions may reflect vulnerabilities related to their sexual offending [4]. Mood problems can also lead to the use of sex as a coping strategy which is associated with a greater likelihood of sexual offending [4] [30] [46]. Persons with lower cognitive abilities may have poorer judgment or impulse control and thus may be more vulnerable to commit sexual offenses.…”
Section: Discussionmentioning
confidence: 99%